Association Among Serum Perfluoroalkyl Chemicals, Glucose Homeostasis, and Metabolic Syndrome in Adolescents and Adults - Lin, Chien-Yu; Chen, Pau-Chung; Lin, Yu-Chuan; Lin, Lian-Yu (Diabetes care, 2009)
OBJECTIVE: Perfluoroalkyl chemicals (PFCs) have been used worldwide in a variety of consumer products. The effect of PFCs on glucose homeostasis is not known. RESEARCH DESIGN AND METHODS: We examined 474 adolescents and 969 adults with reliable serum measures of metabolic syndrome profile from the National Health and Nutrition Examination Survey 1999-2000 and 2003-2004. RESULTS: In adolescents, increased serum perfluorononanoic acid (PFNA) concentrations were associated with hyperglycemia (odds ratio [OR] 3.16 [95% CI 1.39-7.16], P < 0.05). Increased serum PFNA concentrations also have favorable associations with serum HDL cholesterol (0.67 [0.45-0.99], P < 0.05). Overall, increased serum PFNA concentrations were inversely correlated with the prevalence of the metabolic syndrome (0.37 [0.21-0.64], P < 0.005). In adults, increased serum perfluorooctanoic acid concentrations were significantly associated with increased β-cell function (β coefficient 0.07 ± 0.03, P < 0.05). Increased serum perfluorooctane sulfate (PFOS) concentrations were associated with increased blood insulin (0.14 ± 0.05, P < 0.01), homeostasis model assessment of insulin resistance (0.14 ± 0.05, P < 0.01), and β-cell function (0.15 ± 0.05, P < 0.01). Serum PFOS concentrations were also unfavorably correlated with serum HDL cholesterol (OR 1.61 [95% CI 1.15-2.26], P < 0.05). CONCLUSIONS: Serum PFCs were associated with glucose homeostasis and indicators of metabolic syndrome. Further clinical and animal studies are warranted to clarify putative causal relationships.